An Amino‐Functionalized Metal‐Organic Framework, Based on a Rare Ba12(COO)18(NO3)2 Cluster, for Efficient C3/C2/C1 Separation and Preferential Catalytic Performance. Issue 9 (4th December 2017) - Fan, Weidong; Wang, Yutong; Zhang, Qian; Kirchon, Angelo; Xiao, Zhenyu; Zhang, Liangliang; Dai, Fangna; Wang, Rongming; Sun, Daofeng
Abstract: A barium(II) metal‐organic framework (MOF) based on a predesigned amino‐functionalized ligand, namely [Ba2 (L)(DMF)(H2 O)(NO3 )1/3 ]⋅ DMF⋅ EtOH⋅ 2 H2 O (UPC‐33) [H3 L=4, 4′‐((2‐amino‐5‐carboxy‐1, 3‐phenylene)bis(ethyne‐2, 1‐diyl))dibenzoic acid] has been synthesized. UPC‐33 is a 3‐dimensional 3, 18‐connected network with fcu topology with a rare twelve‐nuclear Ba12 (COO)18 (NO3 )2 cluster. UPC‐33 shows permanent porosity and a high adsorption heat of CO2 (49.92 kJ mol −1 ), which can be used as a platform for selective adsorption of CO2 /CH4 (8.09). In addition, UPC‐33 exhibits high separation selectivity for C3 light hydrocarbons with respect to CH4 (228.34, 151.40 for C3 H6 /CH4, C3 H8 /CH4 at 273k and 1 bar), as shown by single component gas sorption and selectivity calculations. Due to the existence of −NH2 groups in the channels, UPC‐33 can effectively catalyze Knoevenagel condensation reactions with high yield, and substrate size and electron dependency. Abstract : Easy separation : An amino‐functionalized and Ba12 (COO)18 (NO3 )2 based microporous metal−organic framework (UPC‐33 ) exhibits high separation selectivity for C3 light hydrocarbons with respect to CH4 and effectively catalyze Knoevenagel condensation reactions.